EFFECT OF WORK POSTURE ON MUSCULOSKELETAL SYMPTOM AMONG TAILORS IN PALEMBANG - Fadillah; Selvi Triani; Rury Tiara Oktariza (PT. Hasba Edukasi Mandiri, 2026)
Tailors are one of the professions at risk of experiencing musculoskeletal complaints due to work posture, such as prolonged sitting and repetitive movements. The purpose of this study is to determine the effect of work posture and musculoskeletal complaints among tailors in Palembang. This research employed an observational analytic method with a cross-sectional approach. The sampling technique used in this study was accidental sampling, with a total of 97 participants consisting of 46 males and 51 females. The age distribution included 29.9% aged ≤ 35 years and 70.1% aged > 35 years. The Rapid Entire Body Assessment (REBA) method was used to evaluate work posture risk, while the Nordic Body Map (NBM) questionnaire was used to identify musculoskeletal complaints. Data analysis was conducted using univariate and bivariate methods with the chi-square test. Based on the REBA calculation, 75.3% of the participants were found to have a moderate risk work posture, and 24.7% had a high-risk work posture. The NBM questionnaire results showed that 78.4% of participants had mild complaints, and 21.6% had moderate complaints. Statistical analysis revealed a significant relationship between work posture and musculoskeletal complaints among tailors in Palembang (p-value 0.002).